2012
DOI: 10.1007/s12028-012-9769-y
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Cerebral Vasospasm Following Resection of a Medulloblastoma in a Child

Abstract: This case illustrates an unusual complication of posterior fossa tumor resection, and the potential utility of TCD studies in the detection and management of vasospasm in pediatric neurocritical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Adult CVS has been reported following open and endoscopic tumor resection [6-11, 13, 16, 20-24] and after rupture or resection of colloid and dermoid cysts [25, 26]. The suspected vasospasm triggers discussed in these cases include chemical meningitis [9, 11, 24, 27], intraoperative bleeding, subarachnoid blood, intracranial hypotension, vasoactive tumor antigens, intraoperative vessel manipulation, and Gelfoam [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adult CVS has been reported following open and endoscopic tumor resection [6-11, 13, 16, 20-24] and after rupture or resection of colloid and dermoid cysts [25, 26]. The suspected vasospasm triggers discussed in these cases include chemical meningitis [9, 11, 24, 27], intraoperative bleeding, subarachnoid blood, intracranial hypotension, vasoactive tumor antigens, intraoperative vessel manipulation, and Gelfoam [19].…”
Section: Discussionmentioning
confidence: 99%
“…The suspected vasospasm triggers discussed in these cases include chemical meningitis [9, 11, 24, 27], intraoperative bleeding, subarachnoid blood, intracranial hypotension, vasoactive tumor antigens, intraoperative vessel manipulation, and Gelfoam [19]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 The DTT tract is the main outflow of the cerebellum, and it has been suggested that injury to the cerebellum and degeneration of this cerebrocerebellar pathway may be involved in cognitive dysfunction and PFS. 13,[27][28][29] More recently, DTI metrics have shown tensor changes in the DTT pathway in patients treated for PF tumor, suggesting that DTI may be more robust than conventional MR imaging in probing structural damage. 12,13,16,30 While prior studies have reported decreased FA of the SCP or increased MD of the cerebellar white matter in patients with PFS when examined at variable single-time points, our results show that the tensor changes may not be limited to those with symptoms of PFS.…”
Section: Discussionmentioning
confidence: 99%